Peningkatan Literasi Biodiversitas Menggunakan Model Kebun Botani di Madiun - Laurensia Maria Yulian Dwiputranti Darmoatmodjo; Indah Epriliati; Paini Sri Widyawati; Agus Purwanto; Leo Eladisa Ganjari (Warta LPM, 2024)
The improvement of literacy on biodiversity growing in the residential areas can support the attitude of society to sustain the ecology, even improving the life quality based on local potentials. However, there are limited live-learning facilities available for biodiversity education. Hence, a community service was carried out by the Study Program of Biology and Study Program of Food Technology, Faculty of Agricultural Technology, Widya Mandala Surabaya Catholic University, Indonesia. Its objective was to improve literacy on biodiversity of the societal partners through knowledge enrichment and awareness of biodiversification potentials which grow in their residential areas. The societal partners are alumni, high school students (St. Bonaventura and the 6th State High School, Madiun), and Pemberdayaan Kesejahteraan Keluarga (PKK) group “Asman Toga” from Rejomulyo village, Madiun; totally 45 participants. The activities included (a) building a botanical garden named Arbor Vitae”, (b)focused group discussion (FGD), and (c) workshop.  Currently, it finished a clearing land and planting more than 50 species for foods and nutraceutical/medicinal sources as well as ecological services. The “Arbor Vitae” had been embedded into university institution by appointing a management in charged. Meanwhile, the improvement of literacy was measured from pre- and post-test during FGD which indicated a significant increase in partners’ literacy by 45.44%; after screening 18 respondents completely filled the tests. The test statements grouped into four indicators of literacy on biodiversity. Moreover, the workshop was complementarily improving the partners’ skill with technology of telang flower jelly drink, purslane medical simplisia, and water clarification using moringa seeds.